Picture perfect autumn : [large type] a novel - Noble, Shelley (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
Discovering old photos in which she sees what her work is missing, Manhattan photographer Dani Campbell searches for their source, which leads her to eighty-year-old Lawrence Sinclair who agrees to mentor her until his estranged grandson arrives believing she's a fortune hunter.